The Determinant of Employee Engagement - Siswanto Siswanto; Ajeng Ekowati Lestari (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2019)
Employee engagement is a significant work attitude to reach the organization’s goal. The employee engagement includes improving the employees’ responsibilities, motivating the co-workers, and influencing the employees’ performance. Accordingly, a study in line with the determinant of employee engagement is needed. The purpose of this study is to analyze the determinant of employee engagement. This study used quantitative approach. The samples of this research were 187 employees of manufacturing company in Mojokerto city. Data retrieval used a questionnaire. The sampling technique used proportional random sampling. Data analysis used path analysis. The result of the study showed that financial compensataion and job satisfaction were determinant of employee engagement. The financial compensation and job satisfaction improve the employee engagement. Whereas, the non-financial compensation does not influence the employee engagement.[Employee engagement merupakan salah satu sikap kerja yang penting untuk mencapai tujuan organisasi. Employee engagement dapat meningkatkan tanggung jawab karyawan, memotivasi rekan kerja dan mempengaruhi kinerja karyawan. Oleh karena itu, studi tentang determinan employee engagement diperlukan. Tujuan penelitian ini adalah menganalisis determinan employee engagement. Penelitian ini menggunakan pendekatan kuantitatif.  Jumlah sample sebanyak 187 karyawan perusahaan manufaktur di Kota Mojokerto.  Pengambilan data melalui kuesioner.  Sedangkan, teknik pengambilannya menggunakan proporsional random sampling.  Analisis data menggunakan analisis jalur.  Hasil penelitian menunjukkan determinan employee engagement adalah kompenansial finansial dan kepuasan kerja. Kompensasi finansial dan kepuasan kepuasan kepuasan kerja meningkatkan employee engagement. Sedangkan, kompensasi non finansial tidak berpengaruh terhadap employee engagement.]